Muslim community perception towards tourism development in Sabang, Aceh, Indonesia - Yusuf, Myna Agustina (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2015)
This study examines the perceptions of the Muslim community regarding tourism development in Sabang, Aceh, Indonesia. Sabang is a tourist destination and is predominantly inhabited by Muslims, hence it applies the Syariah law from the higher level (Aceh Province). Since there has been a gradual increase in the number of tourists from 2009, it brings into question the Muslim community's perceptions and desires of tourism, where there is a clear divide in Muslims, some considering it an unlawful and useless activity, while others encouraging it. This study adopted both the quantitative and qualitative approaches to assess the perception of the Sabang community in the tourism industry. The probability method of simple random sampling techniques was used to decide the respondents of questionnaire survey. 157 respondents were picked and four stakeholders were interviewed, and the outcomes were analysed accordingly. Based on frequency analysis and transcript, the results revealed that both community and stakeholders perceive tourism development in Sabang are not being in line with the community expectations and Aceh identity/law, however they did agree with the established tourism policies. The community considered tourism as an entertainment that must be in compliance with Islam. In particular, the community agreed with the covering of aurah and prohibition of co-habitation of unmarried Muslim tourists. Further analysis of correlation showed that there were no significant relationships between education, religiosity and some perception variables, such as tourism for seeking fun, tourists' attire, and so forth. This might be due to data distribution and acquisition. This study recommended that Sabang authority to establish regulation pertaining to dress code, accommodation for unmarried couples, halal food, and appropriate signage, in addition to conduct regular awareness campaigns among tourism business operators and community regarding tourism activities in Sabang.